A New York Christmas : a novel - Perry, Anne (Ballantine Books, 2014)
"Anne Perry's new Christmas novel is an irresistible tale of love, betrayal, greed, murder, and selfless devotion. For the first time, Perry's annual yuletide offering is set in New York City--a sparkling young metropolis bursting with life, promise, and subtle menace. The year is 1904. Twenty-three-year-old Jemima Pitt, the daughter of Thomas Pitt, head of the Special Branch of the Metropolitan Police, is crossing the Atlantic as companion to Delphinia Cardew, who is to marry the aristocratic Brent Albright in a high-society New York wedding--a grand affair that will join together two fabulously wealthy families, titans of the international financial world. But Jemima senses a mysterious shadow darkening the occasion. Missing from the festivities is Delphinia's mother, Maria, who is marked by disgrace. Nearly sixteen years ago, Maria abandoned young Delphinia and disappeared--and now the Albrights refuse to mention her name. But when Harley, the groom's charismatic brother, asks Jemima to help him search for Maria and forestall the scandal that would surely follow if the prodigal parent turned up at the wedding, she agrees to assist him. From Hell's Kitchen to Fifth Avenue, the Lower East Side to Central Park, Jemima trudges through strange, snowy streets, asking questions but getting few answers--and never suspecting that she is walking into mortal danger, from which not even a handsome young police officer named Patrick Flannery may be able to protect her. Once more, Anne Perry delivers a suspenseful, deeply moving novel that captures the essence of the holiday spirit. Praise for the Christmas novels of Anne Perry "Perry's Victorian-era holiday mysteries. are for many an annual treat."--The Wall Street Journal A Christmas Hope "Very much recommended. a wonderful story."--Historical Novel Review A Christmas Garland "In Anne Perry's gifted hands, the puzzle plays out brilliantly."--Greensboro News & Record A Christmas Homecoming "Could have been devised by Agatha Christie. [Perry is] a modern master."--Pittsburgh Post-Gazette A Christmas Odyssey "[Perry] writes with detail that invades the senses."--Lincoln Journal Star A Christmas Promise "Poignant. should be on the Christmas stocking list of anyone who likes a sniffle of nostalgia."--The Washington Times"--